Reducing the Spread of Covid-19 by Buying Healthy Vegetarian Food at Home (Aplikasi Vege! Mengurangi Penyebaran Covid-19 Dengan Membeli Makanan Sehat Vegetarian Dirumah) - Andhika (Universitas Putra Indonesia YPTK Padang, 2020)
Covid19 is a deadly virus that has been destroyed by the people of the world to be destroyed. Many countries are competing to close their countries from migrants who turn to spread the virus. All shops, whether restaurants or staple food vendors, stop selling. The seller is afraid of the transmission of the virus caused by touch or distance between humans that are too close. Spread through banknotes was allegedly the highest factor in disease transmission. Therefore we developed a payment method into the application without involving banknotes. The seller is still safe selling food everywhere, because payments can be made digitally in the vege application. Thus the community will remain calm while it is working on independent isolation at home during the pandemic. Applications that are designed using Android are expected to be able to reach most people who have an Android phone from other phones. The vege application is a vegetarian food sales application that is low capacity and can be installed by most versions of Android even though old school phones are all. Buyers do not need to come to a restaurant or place to buy food to buy food. Buyers only need to order and pay through the application for vegetarian food purchases. In this way it is expected to reduce the spread of covid 19 virus through banknotes.